Polimorfisme Gen Angiotensin Converting Enzyme pada Hipertensi - Atika Indah Sari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Hypertension is a multifactorial disease with a significant contribution to global cardiovascular morbidity and mortality. In addition to environmental factors, genetic aspects are known to play an important role in the pathogenesis of essential hypertension. One of the most extensively studied candidate genes is the angiotensin-converting enzyme (ACE) gene, particularly the insertion/deletion (I/ccD) polymorphism in intron 16. This article aims to systematically review the scientific evidence regarding the association between ACE gene polymorphism and the occurrence of hypertension. A literature search was conducted through various international scientific publications addressing the biological mechanisms of ACE, the distribution of I/D genotypes, and their association with hypertension risk across different populations. The review findings indicate that the deletion (D) allele is associated with increased plasma and tissue ACE activity, leading to elevated production of angiotensin II and enhanced degradation of bradykinin, thereby contributing to vasoconstriction and increased blood pressure. Several observational studies and meta-analyses report that the DD genotype or the presence of the D allele is associated with an increased risk of essential hypertension in various ethnic groups, although inconsistencies in results across populations have been observed. Differences in genetic background, environmental factors, and research methodologies are thought to influence these variations. Overall, ACE gene polymorphism, particularly the I/D variant, plays an important role in the pathophysiology of hypertension and has the potential to serve as a basis for the development of genetic-based predictive and therapeutic approaches in the future.